Transgender and anxiety: a comparative study between transgender people and the general population - Bouman, Walter Pierre; Claes, Laurence; Brewin, Nicky; Crawford, John R.; Millet, Nessa; Fernandez-Aranda, Fernando; Arcelus, Jon (Taylor & Francis, 2016)
Background: Anxiety disorders pose serious public health problems. The data available on anxiety disorders in the transgender population is limited by the small numbers, the lack of a matched controlled population and the selection of a nonhomogenous group of transgender people.